Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) dan Deteksi Karies di Komplek Bumi Cahaya Bintang Kelurahan Sungai Besar - Amy Nindia Carabelly; Juliyatin Putri Utami; Agung Satria Wardhana; Dewi Puspitasari; Mira Hadistiana; Gita Puspa Ningrum (Jurnal Pengabdian Sumber Daya Manusia, 2022)
Background: Fostering Clean and healthy lifestyle (CHL) and Early Detection of Caries is an effort to create and preserve hygiene and health-oriented life behaviors in the community, so that people can be independent in preventing and overcoming the health problems they face. Methods: Pretest basic knowledge about clean and healthy behavior patterns in the family environment, Conduct CHL Counseling and Training, how to process food properly, detect caries, and conduct post tests. Processing, Analysis, and Presentation of Data: By carrying out community service activities, it is expected to provide benefits, especially for the RT 49 RW 08 Complex Bumi Cahaya Complex to gain an understanding and proper CHL techniques, as an effort to maintain the acceleration of changes in health behavior that occur as a result of the COVID-19 pandemic and can practice how to detect caries early and take preventive measures so that it can improve the quality of life of the people of RT 49 RW 08 Komplek Bumi Cahaya Bintang, South Banjarbaru District. Based on the results of the pre-test and post-test, there was an increase in participants' knowledge from a higher percentage of knowledge. The results of statistical tests using Wilcoxon obtained a P-value of 0.004 which means P <0.05, which means that there is an average difference between the value of knowledge before the pretest and post-test. Conclusion: Educational activities have been effective in increasing the knowledge of PKK mothers RT 49 RW 08 Bumi Cahaya Bintang Complex.